(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to estimate the phenotypic and genetic factors for total milk yield (TMY) in Holstein-Friesian cattle under Libyan conditions, assess the contribution of different factors to the total variance, and estimate heritability to guide future selection programs. Data were collected from 979 production records of Holstein-Friesian cows at the Ghout Sultan Agricultural Project, eastern Libya, between 1985 and 1998. A mixed linear model was applied including random effects (sire, dam, lactation period) and fixed effects (month of calving, year of calving, parity). Variance components were estimated using the REML (Restricted Maximum Likelihood) method as implemented in the MIXED procedure of SAS. Heritability (h²) was calculated from variance components. The mean TMY was 9180.46 kg with moderate phenotypic variability (CV = 26.22%). Lactation period, year of calving, and parity had highly significant effects on TMY (P < 0.0001), while month of calving showed a marginal effect (P = 0.07). Sire and dam effects were not statistically significant (P > 0.05). Sire variance was 366,551.4, dam within sire variance was 1,235,646.1, and error variance was 4,305,434.8. The heritability estimate for TMY was 0.248, indicating that about 24.8% of the phenotypic variation is due to additive genetic effects. It was concluded that lactation period, year of calving, and parity significantly affected TMY, while month of calving showed a marginal effect. Sire and dam effects were not significant, likely due to reliance on imported, non-adapted semen. Genetic improvement is feasible under Libyan conditions; however, establishing a locally adapted breeding program using proven sires is recommended.it concluded that